Oro-Facial and Dental Problems in High Altitude: a Study on Aircrew of Bangladesh Air Force - Sajib, S M Mahfuzur Rahman; Ahsan, Mohammad Ahmed; Haque, Md Ziaul; Mridha, Khairul Islam; Islam, Jakirul; Tarafder, Saiduzzaman; Islam, AFM Shariful; Ahmed, Tahsina (Bangladesh Armed Forces Medical Journal, 2025)
Background: Maintaining optimal dental health is vital for military aircrew to ensure performance and readiness, avoid complications during deployment in remote locations and minimize the risk of dental emergencies. High-altitude exposure poses unique physiological challenges that impact orofacial and dental health among aircrew members. Barotrauma presents several forms, including barodontalgia (altitude-induced dental pain), barosinusitis, barotitis, and odontocrexis (tooth explosion due to pressure fluctuations), each having its own clinical presentation and implications. This study aims to examine the prevalence and factors associated with aviation-induced orofacial and dental problems experienced by aircrew during high-altitude missions, develop preventive techniques, and promote awareness among aviators. Methods: A descriptive, cross-sectional study was conducted in a Medical Squadron consisting of 169 aircrew ranging between the ages of 23 and 58 years. The Bangladesh Air Force (BAF) aircrew who visited the medical inspection department with complaints of orofacial and dental problems within a year were considered as study participants. Results: The mean age of participants was 35.10 ± 9.009 years. The majority (67.46%) reported experiencing barotrauma, with barotrauma-induced sinusitis affecting 22.49% and barodontalgia impacting 30.59%. Pulpitis (20.71%) was the primary cause of barodontalgia. Furthermore, younger age and less flying experience were significantly associated with a higher incidence of barotrauma (p < 0.05). Conclusion: The research explores that orofacial and dental issues linked to high altitude are a significant concern for young and less experienced aircrew, highlighting the pathophysiology and prevention of these problems. Bangladesh Armed Forces Med J Vol 57 No (2) December 2024, pp 36-43